Cognitive–behavioural therapy for non-motor symptoms of Parkinson's disease: a clinical review. Issue 1 (10th January 2017) - Koychev, Ivan; Okai, David
Abstract : Neuropsychiatric symptoms are common in Parkinson's disease (PD) and have a disproportionate impact on quality of life and carer burden. Pharmacological treatment is the main approach in dealing with these symptoms, but it is limited by variable efficacy and risk of drug interactions. Non-pharmacological approaches using the cognitive–behavioural therapy (CBT) model are viable alternatives and in this review paper we summarise the evidence of CBT for three of the most common psychiatric manifestations of PD: depression and anxiety, impulse-control disorders and insomnia. Most studies modified the usual CBT format to include modules accounting for problems specific to PD: activity scheduling around motoric function, motor symptoms as triggers of anxiety, fear of falling and preparation for disease progression as well as accommodation of materials for suspected executive dysfunction. We found a growing evidence base that CBT (modified to account for PD-specific problems) is effective in the treatment of PD psychiatric symptoms. Where controlled study design was used, moderate effect sizes are reported for the efficacy of CBT for depression, including with distance administration of CBT. The effects were sustained during follow-up which was between 1 and 6 months. In addition, there are some initial data on the effects of CBT on impulse-control disorders and insomnia. The studies were limited by their small and potentially unrepresentative samples and the quality of sample reporting (eg, concomitant antidepressant and dopaminergic therapy use). Additional well-designed and adequately powered studies are required to determine the utility of CBT in PD.